The modernisation of umpire development: Netball New Zealand's reforms and impacts. Issue 3 (27th May 2018) - Sam, Michael P.; Andrew, Joyce C.; Gee, Sarah
ABSTRACT: Research question: Officiating structures are under increasing pressure to 'modernise', raising the need to understand and appraise the suite of reforms aimed at modernising umpire development. The study explores how modernisation has impacted on officiating stakeholders at community and development levels. It investigates how stakeholders have responded to modernisation's institutional 'logics' (e.g. continuous improvement, alignment) and its associated technologies (e.g. accreditations, whole-of-sport planning). Research methods: The study draws from a detailed case analysis of New Zealand's largest women's sport organisation: Netball New Zealand (NNZ). Methods include document analysis, semi-structured interviews with national officiating panel members ( n  = 4) and focus groups with zone representatives (two groups with four participants in each). This study combined inductive and deductive analyses. Results and findings: NNZ emphasised growth and continual improvement by establishing targets and initiating programmes to support more squads and levels of accreditation. It elicited specialist governance structures in umpiring through the addition of regional panels, while pursuing alignment and 'joined-up' operations through the advancement of pathways and the integration of athlete development strategies into umpiring. Implications: Modernisation reforms (such as umpire pathways) can lead to increasing volunteer workloads, a greater focus on youth and the emergence of an achievement culture concerned with standards, qualifications and incentives. Modernisation may thus improve youth recruitment, but does not necessarily solve retention problems. This study advances the importance of considering the consequences of modernisation on the capabilities of sport organisations.